Utilization Utilization of E-Commerce in Efforts to Increase Sales of Micro Small Medium Enterprises (MSMEs) in Kelurahan Kampung Empat, Tarakan City. - Nurul Hidayat; Inang Aria Arifin (International Journal Of Community Service, 2021)
Currently, information technology has become a necessity that organizations or companies must own to improve each service produced. The growing evidence of this and the easy role of information technology and information systems among organizations for large businesses and many Micro, Small, and Medium Enterprises (MSMEs) can survive in the face of increasingly fierce competition today. Tarakan City Statistics in 2020 recorded as many as 13,427 MSMEs spread in Tarakan City. These data indicate an increase in the number of SMEs in Tarakan City. The number of new businesses emerging requires these business actors to survive and compete to maintain the sustainability of their business. The outputs produced in this PKM activity include 1) Increased knowledge and ability of the community regarding online-based technology, especially the online shop for Micro, Small, and Medium Enterprises (MSMEs) in the Kampung Empat area ​​Tarakan City. 2) Micro, Small, and Medium Enterprises (MSMEs) have online stores that they can manage independently. 3) Micro, Small, and Medium Enterprises (MSMEs) can be more motivated to understand the use of existing technology. Business people can increase their business activities (buying and selling), either their products or outside products from online stores.